2012
DOI: 10.1177/1350650112455783
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of lubrication characteristics of a tilting pad thrust bearing disturbed by a water-contaminated lubricant

Abstract: The effect of water contamination on the lubrication has been described in several studies. Water has been defined as a dangerous contaminant which has a very detrimental impact on bearing performance. Nevertheless, many of the previous studies are based on post-accidental analyses, made after the lubrication failure. Thus, these analyses do not take into account all the possible conditions of the presence of water in the oil that can describe the situation. For instance, the case of water-in-oil fine emulsion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…in which Equations (10) and (11) have been obtained by imposing the dynamic balance of the centre of the disc C. Equations (12) and (13) have been derived from the dynamic balance of the centre of the Journal J.…”
Section: Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…in which Equations (10) and (11) have been obtained by imposing the dynamic balance of the centre of the disc C. Equations (12) and (13) have been derived from the dynamic balance of the centre of the Journal J.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…In the last few years, research has demonstrated that the oil whirl occurs when the journal bearing operates with micropolar lubricant [6][7][8][9][10]. For this reason, the effect of the contamination of the lubricants [11] and of non-linear behaviour of film-oil journal bearings in rotating machines have been studied by many authors [12]. Harika et al investigated the effect of water contamination of lubricants on hydrodynamic lubrication and the results show that the viscosity of the lubricant is modified by the presence of water in the lubricating oil.…”
Section: Introductionmentioning
confidence: 99%
“…Glavatskih and colleagues [3][4][5] developed a thrust bearing test rig, which could measure the film temperature and frictional torque. Harika et al 6 experimentally studied the effect of water contamination on the tilting-pad thrust bearings lubrication. An eight shoes tilting-pad thrust bearing supplied with water-contaminated oil in which the contamination rate reached 10% of water by mass was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Heinrichson and Fuerst 1 performed experimental investigation of the influence of an oil injection pocket on the pressure distribution and oil-film thickness. Measurements of the pressure and oil-film thickness distributions were presented for tilting-pad thrust bearing with surface area of the pad around 100 cm 2 .…”
Section: Introductionmentioning
confidence: 99%